UKRAINE'S INTERNATIONAL POLICY WITH HUNGARY: PROBLEMATIC ISSUES IN THE FIELD OF INTERNATIONAL RELATIONS - Секунова, Юлия; Гаврилюк, Юлия (SWorldJournal, 2021)
The article analyzes the international policy of Ukraine with Hungary from the beginning of the recognition of independent Ukraine by Hungary to the present day. After the collapse of the Soviet Union in 1991, it was important for Hungary and Ukraine to e